(—2m+n—p)(2m—n—p)急求啊~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
2个回答
=-(2m-n+p)(2m-n-p)
=-[(2m-n)+p][(2m-n)-p]
=-[(2m-n)²-p²]
=-(4m²-4mn+n²-p²)
=p²-4m²+4mn-n²
相关问题
(m-2n-p)(m-2n+p)-(m+2n+p)(m+2n+p)
M+2N-P=M+() m-2n+p=m-() m-2n-p=m-() m+2n+p=m-()
(2m+n-p)( 2m+p-n)
已知m,n,p满足|2m|+m=0,|n|=n,p•|p|=1,化简|n|-|m-p-1|+|p+n|-|2n+1|.
已知m、n、p满足|2m|+m=0,|n|=n,p|p|=1.化简:|n|-|m-p-1|+|p+n|-|2n+1|.
计算:(2m+n-p)(2m-n+p)
下列变形中错误的是( ) A.m 2 -(2m-n-p)=m 2 -2m+n+p B.m-n+p-q=m-(n+p-q
已知m,n.p都是整数,且|m-n|^3+|p-m|^5=1,求|p-m|+|m-n|+2|n-p|的值
化简(m+2n-3p)2-(m-2p)(m-n)
若实数m,n,p满足m-n=8,mn+p^2+16=0,求m+n+p的值